Modelling and optimization of a laser droplet-formation process - Kokalj, Tadej (Materiali in tehnologije, 2013)
The laser droplet-formation process (LDFP) is a part of the novel joining technology for forming high-temperature joints. The advantages of this technology are: good heat-input control, good control of the added material and limited local heating. A molten metal droplet is used as the basic unit for the filling material, and a determination of the process parameters for the formation of droplets with desired properties is crucial. A physical and numerical model of the process was built to allow a theoretical determination of the process parameters. The numerical model enables a simulation of the process at different sets of parameters and a genetic algorithm optimization was implemented to find the best set. To verify this general procedure for determination and optimization of the parameters, we applied it in a specific case of a nickel wire. On the basis of the numerical model of the process, laser pulses for pendant-droplet formation and droplet detachment were determined and applied in experiments. With numerically determined laser pulses pendant-droplet formation and detachment were accomplished. In most cases, the process showed a very high repeatability. The encouraging experimental verification shows that a numerical approach is a very helpful tool for a determination of the process parameters and a better understanding of the process. It significantly reduces the number of necessary experiments when the laser droplet-formation setup or the target droplet properties are changed.
Keywords: lasersko varjenje; nikelj; modeliranje; optimizacija